Pengaruh Komitmen Organisasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Pt. Bpr Insumo Sumberarto Kediri - Hari Santosa; Enni Sustiyatik; Budi Rahayu; Djunaedi Djunaedi (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2022)
This study aims to determine the effect of Organizational Commitment on Employee Performance with Job Satisfaction as an Intervening Variable at PT. BPR Insumo Sumberarto Kediri. This type of research uses a descriptive quantitative survey approach where the questionnaire will be distributed to all research respondents. The population in this study was 60 respondents, all of whom were used as samples, also known as census research. The path analysis method tests the results of the respondent's data to measure the effect of the intervening variable. The test results show that organizational commitment positively and significantly affects employee job satisfaction. With a strong commitment, employees will be encouraged to work hard for progress to achieve job satisfaction and employee performance by the expectations desired by the organization. Organizational commitment has a positive and significant effect on employee performance. With the better and more consistent organizational commitment that is currently implemented, it will be able to improve employee performance. Job satisfaction affects employee performance. Where the higher the employee's job satisfaction, the employee will show best performance. By mediating job satisfaction, the effect of organizational commitment on employee performance also increases.